The Impact of The RCEP Agreement on The Export Performance of Indonesia’s Processed Cocoa - Muh. Asharuddin; Harianto; Feryanto (Jurnal Manajemen dan Agribisnis, 2025)
Background: The RCEP trade agreement, which has been in effect since 2023, will undoubtedly play a role in facilitate trade flows by reducing barriers, especially for Indonesia's leading commodity exports in the international market. Purpose: This study analyzes the impact of the Regional Comprehensive Economic Partnership (RCEP) agreement on the export performance of Indonesian processed cocoa commodities in the international market.Design/methodology/approach: The data used are secondary data in the form of panels from 2018 to 2024, with cross sections in the form of quarters. The research method uses Difference in Difference (DiD) analysis by looking at changes in performance variables assessed based on diversification value (HHI), export value, and export volume after the agreement's implementation.Findings/Results: The estimation results show that the RCEP trade agreement increases the value by 0.52 units and export volume by 0.68 units, but not diversification. The diversification value of processed cocoa exports in RCEP member countries is lower than that in non-member countries. However, after the implementation period of the agreement in 2023, there are differences in export decisions of member countries.Conclusion: The RCEP trade agreement implementation positively and significantly affected the value and volume of Indonesian processed cocoa exports in the international market but had no impact on diversification.Originality/value (State of the art): This study focuses on the impact of the RCEP on Indonesia's processed cocoa export performance. This study uses 25 central destination countries for processed cocoa exports, with 10 countries in the treatment group and 15 in the control group. Keywords: export performance, processed cocoa, RCEP, trade agreement, cocoa, international market